Construction thoughts and practice of the trainer studio for the training of Traditional Chinese Medicine nursing techniques (中医特色技术护理培训师工作室建设实践与思考) - ZHAO Nan (赵楠); WANG Guiying (王桂英); LIAO Juan (廖娟); MA Yun (马芸); QIU Lina (岳丽娜); TANG Ling (唐玲); HAO Li (郝丽); LI Jing (李静) (中西医结合护理)
Beijing Administration of Traditional Chinese Medicine had set up “Special Funding Program Supporting the development of Traditional Chinese Medicine-Improving the quality and efficacy of Traditional Chinese Medicine”, and two trainer studios for the training of Traditional Chinese Medicine nursing techniques were established: The Trainer Studio for Traditional Chinese Medicine Five-element Music therapy located in Xiyuan Hospital of China Academy of Chinese Medical Sciences, and Yanjing Trainer Studio for Traditional Chinese Medicine External Application located in Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University. The establishment of two trainer studios has achieved outstanding results in the following aspects: innovation on training model of Traditional Chinese Medicine nursing techniques, enriched cultivating mode for Traditional Chinese Medicine nursing staff, standardization and promotion of Traditional Chinese Medicine, establishment of academic platform for Traditional Chinese Medicine. (北京市中医管理局设立“支持中医药事业发展专项经费—中医药提质增效项目”, 在中国中医科学院西苑医院和首都医科大学附属北京中医医院分别成立“中医五行音乐疗法护理培训师工作室”和“燕京中医外治法护理培训师工作室”。在创新中医护理技术的培训模式、丰富中医护理师资的培养模式、促进中医护理技术的规范及推广、搭建中医护理学术科研平台等方面均取得成效, 为其他省市开展中医护理特色技术师资培训提供借鉴思路。)